Effect of Make A Match Learning Model on Student Learning Outcomes on Statistical Materials - Nurfiati Nurfiati; Vera Mandailina; Mahsup Mahsup; Syaharuddin Syaharuddin; Abdillah Abdillah; Eka Fitriani (Unversitas Muhammadiyah Mataram, 2020)
Abstract: The lowest average daily repeat score data is 65 and has not met the minimum completed criteria of 75. The Make a Match model is very helpful in creating an effective learning environment by utilizing the elements that exist in students. This learning model is a game in the form of question cards and answer cards. The purpose of the study was to determine the influence of the Make a Match learning model on students' math learning outcomes. The research design is quasi-experimental with post-test only. Sampling using random sampling method was taken as many as 2 classes as control class and experimental class. Hypothesis testing used t-test, calculation result obtained t-count of 1,688 while t-table value of 1,645, because t_hitung>t_(table) then H_O rejected and hypothesis received. It is concluded that there are differences in learning outcomes between the control class and the experimental class. It is recommended that teachers can continue to develop the Make a Match model. Abstrak: Data nilai ulangan harian siswa rata-rata paling rendah yaitu 65 dan belum mencampai kriteria ketuntasan minimal yaitu 75. Model Make a Match sangat membantu menciptakan lingkungan belajar yang efektif dengan memanfaatkan unsur-unsur yang ada pada siswa. Model pembelajaran ini berupa permainan berbentuk kartu soal dan kartu jawaban. Tujuan penelitian untuk mengetahui pengaruh model pembelajaran Make a Match terhadap hasil belajar matematika siswa. Rancangan penelitian adalah quasi eksperiment dengan post-test only. Pengambilan sampel menggunakan cara random sampling diambil sebanyak 2 kelas sebagai kelas kontrol dan kelas eksperimen. Pengujian hipotesis digunakan uji t, hasil perhitungan diperoleh t-hitung sebesar 1.688 sedangkan nilai t-tabel sebesar 1.645 karena maka ditolak dan hipotesis di terima. Disimpulkan terdapat perbedaan hasil belajar antara kelas kontrol dengan kelas eksperiment. Disarankan guru dapat terus mengembangkan model Make a Match.